A discourse analytic framework for conversational engagement in online discussion tasks. - MARTIN, GILLIAN; O'ROURKE, BREFFNI (My University, 2014)
This paper reports on a long-running telecollaborative exchange between a German and an Irish university. On the Irish side, the exchange is embedded within a course in intercultural communication offered to final-year students of German. The course involves weekly tasks, some inspired by the Cultura model, focused on issues of intercultural communication, and involving text-based chat in small groups. While student response to the course is positive overall, the chat encounters, in the estimation of the instructors, often fall short of the targeted level of engagement with the theoretical issues. There are many possible factors in play: task design and pre-chat briefing; teacher facilitation; constraints of the communications medium; and cultural factors at various levels, but especially at the institutional (German university vs. Irish university) and micro (group) level. In this paper, we will present a discourse-analytic framework for analysing task- and other-engagement on the basis of chat transcripts. We will use it to (i) identify missed opportunities for deeper interpretative and knowledge-building dialogue, and (ii) characterise collaborative engagement on task in a way that may be generalisable to other synchronous, text-based tasks. The framework should also be potentially useful to online task designers for defining desirable discourse outcomes; to instructors, for monitoring and facilitating online discourse; and to learners, for reflecting on the quality of their engagement with tasks, within-institution peers, and telecollaborative partners.
EuroCALL
PRESENTED
Groningen
Keywords: Identities in Transformation; Intelligent Content & Communications; Telecommunications; Applied Linguistics; Conversation and discourse analysis; Information technology in education; Language Acquisition (first & second)